2021
DOI: 10.1155/2021/9924593
|View full text |Cite
|
Sign up to set email alerts
|

MHD Boundary Layer Flow over a Stretching Sheet: A New Stochastic Method

Abstract: In this study, a new computing model is developed using the strength of feed-forward neural networks with the Levenberg–Marquardt scheme-based backpropagation technique (NN-BLMS). It is used to find a solution for the nonlinear system obtained from the governing equations of the magnetohydrodyanmic (MHD) boundary layer flow over a stretching sheet. Moreover, the partial differential equations (PDEs) for the MHD boundary layer flow over a stretching sheet are converting into ordinary differential equations (ODE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Hence, we can extend the same technique to obtain the same benefits on other iterative methods using inverses of linear operators. The method discussed in this paper find applications in the problems listed in [16,17,18,19,20,21]. for x = (x1, x2, x3) T .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we can extend the same technique to obtain the same benefits on other iterative methods using inverses of linear operators. The method discussed in this paper find applications in the problems listed in [16,17,18,19,20,21]. for x = (x1, x2, x3) T .…”
Section: Discussionmentioning
confidence: 99%
“…e AI-based numerical technique was frequently used in di erent applications to solve di erential equations [16][17][18], but there is a need to explore and exploit the stochastic numerical technique based on intelligent computing paradigms to solve and analyze the problems given in Equations ( 14)- (16). A few recently published studies of paramount importance contain mathematical model solution in nonlinear optics [19], atomic physics [20], and nancial models [21,22], eye model [23], COVID-19 virus spread models [24,25], entropy generation system [26,27], and ow problems [28][29][30][31][32][33][34][35][36][37][38][39][40]. According to our literature research, to examine the SFNM between two circular plates, we apply the AI technique through the ANN-LMS to realize nonlinear backpropagation of neural network to Equations ( 14)- (16).…”
Section: Introductionmentioning
confidence: 99%
“…This study solved the modeled problem using the fractionalized Laplace transform technique. A stochastic process to study the hydrodynamic border layer flow concluded an expanding surface was mathematically exemplified by Ullah et al 17 The researchers theoretically examined the tinny film flow of non-Newtonian solutions in the attendance of radiative and dissipative heats. [18][19][20] The role of nanospray on heat transmission enhancement of the hydrodynamic flow above a cylinder was mathematically scrutinized by Khan et al 21 The above work is extended by Usman et al 22 by considering the viscoelastic flow.…”
Section: Introductionmentioning
confidence: 99%